Tribological behavior of a hydrostatically extruded ultra-fine grained Ti-13Nb-13Zr alloy - Bulutsuz, Ash Gunay; Yurci, Mehmet Emin; Ozaltin, Kadir; Chrominski, Witold; Lewandowska, Malgorzata (CARL HANSER VERLAG, 2019)
This contribution summarizes the results an investigation of the wear resistance of as received initial state and nano-structured Ti-13Nb-13Zr alloy obtained by hydrostatic extrusion. The tribological behavior was examined using a ball-on-disc tribometer under unlubricated sliding contact conditions against an Al2O3 ceramic ball. Friction coefficient, material transfer and wear debris of the samples were observed after the wear tests. Wear characteristics of the samples were investigated by means of an optical profilometer, mechanical profilometer and scanning electron microscope for wear debris morphology and wear tracks. Although friction coefficients are very similar according to tribological observations, the domestic distribution of wear characteristics varied for samples of various grain sizes. Morphological observations have shown that surface responses to abrasive ceramic balls involve localized long and short wear debris, fracture, surface plowing causing adhesive wear and the formation of larger surface debris, and material transfer between titanium and the ceramic counterpart.
Keywords: Titanium alloy; beta titanium; plastic deformation; hydrostatic extrusion; TITANIUM-ALLOY; TI; WEAR; STRENGTH; MODULUS; AL; Materials Science